Book Review: Intisari Agama-Agama Sedunia: Sebuah Ringkasan tentang 13 Agama Besar di Dunia - Arthur Aritonang (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Hali, Ph.D, a permanent lecturer at STT Aletheia, wrote this book. This book was written because of the author's experience, who was entrusted with teaching courses on world religion education at Pelita Harapan University. When he investigated the literature on religious books, he found books that were too simple but contained books that went too deep. Hali longs to write a book that will make it easier for general readers who long to learn about religions, whose contents include the essential points regarding the history of religion's founding and its central teachings. The religious boundaries studied in this book include Buddhism, Hinduism, Islam, Jainism, Confucianism, Christianity, Manichean, Sikhism, Shinto, Taoism, Judaism, Zoroastrianism, and Bahai. Furthermore, in the writing systematics section, firstly, the reporter will present only the outline of each chapter and then the conclusion. At the same time, the second part contains a critical analysis of this book.